2019
DOI: 10.1111/mec.15059
|View full text |Cite
|
Sign up to set email alerts
|

Importance of plant‐ and microbe‐driven metabolic pathways for plant defence

Abstract: Expression of plant phenotypes can depend on both plant genomes and interactions between plants and the microbes living in, on and near their roots. We understand a growing number of the mechanistic links between plant genotypes and phenotypes, such as defence against herbivory (see brief review in Hubbard et al., 2019), yet the links between root microbiomes and the comprehensive swathe of plant phenotypes they affect (Friesen et al., 2011) remain less clear. In this issue of Molecular Ecology, Hubbard et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…As our experiment was conducted at low phosphorus, we also explore phosphorus concentrations in particular. Plants may highly mis-express traits under artificial deprivation of soil biota (Partida-Martinez and Heil, 2011;Hubbard et al, 2019;O'Brien, 2019), so we restricted this analysis to inoculated plants, though we projected uninoculated plants onto resulting CCA axes for comparison. We evaluated links between composite axes and fitness using linear models (f itness ∼ axis), fit with MCMCglmm in R. To compare to results for local adaptation, we performed the same linear model analysis as for biomass (above) on the first two CCA axes and the traits most strongly correlated to them (strongest loadings), as well as leaf tissue phosphorus, due to expected links to a key rhizosphere component (AMF, Smith et al, 2010).…”
Section: Characterization Of Field Sites and Collectionsmentioning
confidence: 99%
“…As our experiment was conducted at low phosphorus, we also explore phosphorus concentrations in particular. Plants may highly mis-express traits under artificial deprivation of soil biota (Partida-Martinez and Heil, 2011;Hubbard et al, 2019;O'Brien, 2019), so we restricted this analysis to inoculated plants, though we projected uninoculated plants onto resulting CCA axes for comparison. We evaluated links between composite axes and fitness using linear models (f itness ∼ axis), fit with MCMCglmm in R. To compare to results for local adaptation, we performed the same linear model analysis as for biomass (above) on the first two CCA axes and the traits most strongly correlated to them (strongest loadings), as well as leaf tissue phosphorus, due to expected links to a key rhizosphere component (AMF, Smith et al, 2010).…”
Section: Characterization Of Field Sites and Collectionsmentioning
confidence: 99%
“…In addition to these direct effects on plant performance, plant‐associated microorganisms can also significantly change plant interactions with other species, such as herbivores and pollinators, as well as parasites, pathogens, or mutualists (Berg and Koskella 2018; Fox, 1988; Porter et al, 2020; Simonsen & Stinchcombe, 2014). Belowground mutualists ameliorate the negative effects of plant enemies such as pathogens and herbivores by inducing an immune response that confers systemic resistance against a broad range of enemies (Klein et al, 2012; Morris et al, 2010; O’Brien, 2019; Pieterse et al, 2014). The effect of the soil microbiome on plant species interactions can be surprisingly broad: Recently, Hubbard et al (2019) found that the root microbiome played a larger role in mediating the damage caused by herbivores than plant genotype (Hubbard et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Belowground mutualists ameliorate the negative effects of plant enemies such as pathogens and herbivores by inducing an immune response that confers systemic resistance against a broad range of enemies (Klein et al, 2012;Morris et al, 2010;O'Brien, 2019;Pieterse et al, 2014). The effect of the soil microbiome on plant species interactions can be surprisingly broad: Recently, Hubbard et al (2019) found that the root microbiome played a larger role in mediating the damage caused by herbivores than plant genotype (Hubbard et al, 2019).…”
mentioning
confidence: 99%